PERUBAHAN PERILAKU EMOSIONAL ANAK KELAS V TERHADAP FILM SERIAL ANIMASI TSUBASA - Abdul Syukur; Susilawati Susilawati; Husni Wakhyudin (Jurnal Sinektik, 2018)
The purpose of this study is to know the existence of changes in the emotional behavior of students toward the Tsubasa animated serial film. The approach used in this study is a qualitative research approach. In principle, this qualitative research is a procedure to result a number of descriptions of what is written and what is spoken by people who become the target of research and descriptions of their behavior which can be observed. Qualitative research is neither aiming at measuring nor using procedures in explaining the results of research. This approach is used to explain and describe the focus of research, which is about changes in emotional behavior of fifth grade students to the Tsubasa animated serial film. The appearance of emotional changes of the students out of 38 students in this study as many 21 children experienced high emotional changes, while 17 children experienced moderate emotions.